THE ROLE OF HADITHS IN EDUCATION AND UPBRINGING (International Engineering Journal For Research & Development, 2021)
The article gives good information about the important role of hadiths in education and upbringing. Hadiths are an important source for the education of the people, morality, religious beliefs, as well as the study of the life of the people, its past economic, political and cultural life. It is proved that hadiths have only good influence on people. Several hadiths are explained in the article. To sum up hadiths are a means of transmitting ancient customs, traditions, rituals and customs from generation to generation.